An enclosed medieval farmstead at Great Ellingham, Norfolk - Boyle, Mick (Medieval Settlement Research, 2022)
In 2018–19, geophysical survey and trial trenching in advance of housing development on land between Hingham Road and Watton Road, Great Ellingham, Norfolk (TM018977), highlighted the archaeological potential of the site (Davies 2018), and Informative Trial Trenching recorded the presence of significant archaeological remains (Whitmore 2019). In consequence, NPS Archaeology were commissioned and funded by All Saints Development (Great Ellingham) Limited to carry out excavation and stripping, mapping and sampling of a targeted area covering an apparent ditched enclosure and associated features. The methodologies employed by the project are detailed in the site archive report (Boyle 2021).